Frailty predicts outcome of partial nephrectomy and guides treatment decision towards active surveillance and tumor ablation - Walach, Margarete; Wunderle, Michael; Härtel, Nicolai; Mühlbauer, Julia; Kowalewski, Karl-Friedrich; Wagener, Nina; Rathmann, Nils-Andreas; Kriegmair, Maximilian (World journal of urology, 2021)
To examine frailty and comorbidity as predictors of outcome of nephron sparing surgery (NSS) and as decision tools for identifying candidates for active surveillance (AS) or tumor ablation (TA).
Gesehen am 20.02.2023